The Relationship Between Metacognitive Skills and Motivation of University Students - Aytunga Oguz; Neriman Ataseven (ÜNİVERSİTEPARK Limited, 2016)
The aim of study is to determine the relationship between metacognitive skills and motivation of students in the education faculty. Research in correlational survey method includes 520 university students. "Metacognitive Skills Scale" and "Academic Motivation Scale" are used for data collection. Descriptive statistics, Pearson Correlation Coefficient, t test, ANOVA were used for data analysis. According to findings, there is a positive and significant relationship in low level between metacognitive skills and IMTK, IMTA, IMES, EMID, EMIN, and EMER and a negative and significant relationship in low level between metacognitive skills and AMOT. A significant difference is found on students' metacognitive skills according to grade, status of reading in a month and whether or not having taken a lesson on learning strategies. Furthermore, a significant difference in students' EMID, EMIN, and AMOT according to gender and field, in IMTK, IMTA, IMES, and AMOT according to status of reading in a month and in IMTA and IMES according to whether or not having taken lessons on learning strategies was found.